Study of synthesis variables in the nanocrystal growth behavior of tin oxide processed by controlled hydrolysis - Ribeiro, C.; Lee, EJH; Giraldi, T. R.; Longo, Elson [UNESP]; Varela, José Arana [UNESP]; Leite, E. R. (Amer Chemical Soc, 2004)
Tin dioxide nanoparticle suspensions were synthesized at room temperature by the hydrolysis reaction of tin chloride (II) dissolved in ethanol. The effect of the initial tin (II) ion concentration, in the ethanolic solution, on the mean particle size of the nanoparticles was studied. The Sn2+ concentration was varied from 0.0025 to 0.1 M, and all other synthesis parameters were kept fixed. Moreover, an investigation of the effect of agglomeration on the nanoparticle characteristics (i.e., size and morphology) was also done by modifying the pH of the SnO2 suspensions. The different samples were characterized by transmission electron microscopy, optical absorption spectroscopy in the ultraviolet range, and photoluminescence measurements. The results show that higher initial ion concentrations and agglomeration lead to larger nanoparticles. The concentration effect is explained by enhanced growth due to a higher supersaturation of the liquid medium. However, it was observed that the agglomeration of the nanoparticles in suspension induce coarsening by the oriented-attachment mechanism.